2020
DOI: 10.3390/app10072619
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Two-DOFs Driving Mechanism for a Motion-Assisted Finger Exoskeleton

Abstract: This paper presents a novel exoskeleton mechanism for finger motion assistance. The exoskeleton is designed as a serial 2-degrees-of-freedom wearable mechanism that is able to guide human finger motion. The design process starts by analyzing the motion of healthy human fingers by video motion tracking. The experimental data are used to obtain the kinematics of a human finger. Then, a graphic/geometric synthesis procedure is implemented for achieving the dimensional synthesis of the proposed novel 2 degrees of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…24 A description of the design procedure, including finger motion study, synthesis of the mechanism, and finite element analysis, is presented in ref. 23 Preliminary numerical and experimental validation of ExoFinger is presented in ref. 25 to demonstrate the exoskeleton performance from theoretical to practical viewpoints.…”
Section: Exofinger a Finger Exoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…24 A description of the design procedure, including finger motion study, synthesis of the mechanism, and finite element analysis, is presented in ref. 23 Preliminary numerical and experimental validation of ExoFinger is presented in ref. 25 to demonstrate the exoskeleton performance from theoretical to practical viewpoints.…”
Section: Exofinger a Finger Exoskeletonmentioning
confidence: 99%
“…The above aspects' application gave a conception of the ExoFinger design whose developments and results are reported in refs. 23,24 The article's main contribution is to report an experimental characterization of proper operation of the proposed ExoFinger finger exoskeleton with a variety of sensors for motion control and medical monitoring. In addition, the proposed finger exoskeleton mechanism has a peculiar structure with two degrees-of-freedom (DOF)'s for a full finger motion range while monitoring the motion assistance.…”
Section: Introductionmentioning
confidence: 99%
“…16 The application of 3D printing and virtual simulation technology fulfils the design of the robot prototype and improves the feasibility check of humanmachine interaction. 17,18 Bouteraa et al designed a hand rehabilitation exoskeleton robot in Solidworks that fits the movement characteristics of the finger joints based on the hand structure. The exoskeleton is 3D printed and combined with a virtual reality training system to continuously monitor and evaluate the rehabilitation process, thereby providing useful feedback for patients and therapists.…”
Section: Introductionmentioning
confidence: 99%
“…However, activity or exercising should not cause pain, unusual muscle discomfort, or signs of overuse. [5][6][7] Robotic devices for rehabilitation can assist in improving the increase in resistance, range of motion (ROM), and assist health professionals, as proposed, for example, in the literature. 8,9 The possibility of using robotic devices as an efficient means of providing therapy has been the subject of research involving rehabilitation after stroke, as reported, for example, in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…5 Rehabilitation of human hand or fingers can be a promising application for robotics. 6,7 Gradual increases in the number of repetitions of the exercise increase the resistance to fatigue; likewise, progressive increases in resistance can increase strength. However, activity or exercising should not cause pain, unusual muscle discomfort, or signs of overuse.…”
Section: Introductionmentioning
confidence: 99%